THE MANAGEMENT OF PERIAPICAL MAXILLARY CYST BY USING THE A-PRF (PLATELET RICH ADVANCED FIBRIN) A CASE REPORT - Mihaela Mitrea; Anca Rusu; Dorelia Lucia Călin (Romanian Society of Oral Rehabilitation, 2015)
Periapical or radicula cysts are the most common inflammatory cysts of the jaw. The surgical intervention aims to remove periapical pathology to obtain bone regeneration and healing of periapical tissues. Improving the regeneration of the human body by using the the patient's own blood is a unique concept in dentistry. The purpose of this case report is to illustrate the effectiveness of advanced platelet-rich fibrin (A-PRF) inserted into the bone defect resulting from a periapical cyst enucleation. The physiological time of healing of the cystic cavity is from 6 months to 1 year, but when the cystic cavity is filled with A-PRF, this phenomenon of physiological healing is accelerated, the healing period decreasing to three months. The results of this case report shows that APRF can be used successfully as monotherapy for obtaining periapical regeneration.